2017
DOI: 10.15242/ijacebs.c0317025
|View full text |Cite
|
Sign up to set email alerts
|

Chemical study of Dodonaea viscosa planting in Iraq

Abstract: Abstract-Dodonaea viscosa Linn. is distinguished therapeutic plant where the leaves are utilized as calming, hostile to ulcer, against bacterial and antifungal operators and in the treatment of breaks. In perspective of its restorative significance and compound investigation were done, these studies gave referential data to distinguishing proof of this crude medication.Various substance constituents have been confined from Dodonaea viscosa, however the vast majority of these were directed to the species gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In Iraq, D. viscosa is grown and propagated as an ornamental plant used for decoration, shading and hedging, due to its rapid growth rate and high tolerance to drought (Gilman 1999). Also, chemical analysis showed that D. viscosa has chemical compounds which could potentially be used for medicinal, insecticidal, and pharmaceutical applications (Hamadi 2017).…”
Section: Rapid Communicationmentioning
confidence: 99%
“…In Iraq, D. viscosa is grown and propagated as an ornamental plant used for decoration, shading and hedging, due to its rapid growth rate and high tolerance to drought (Gilman 1999). Also, chemical analysis showed that D. viscosa has chemical compounds which could potentially be used for medicinal, insecticidal, and pharmaceutical applications (Hamadi 2017).…”
Section: Rapid Communicationmentioning
confidence: 99%